Impact of a shorter replacement interval of plastic stents on premature stent exchange rate in benign and malignant biliary strictures. Issue 6 (17th March 2022) - Kubesch, Alica; Görnert, Fabian; Filmann, Natalie; Bojunga, Jörg; Zeuzem, Stefan; Jung, Michael; Friedrich‐Rust, Mireen; Walter, Dirk
Abstract: Background and Aim: The main disadvantage of plastic stents is the high rate of stent occlusion. The usual replacement interval of biliary plastic stents is 3 months. This study aimed to investigate if a shorter interval of 6–8 weeks impacts the median premature exchange rate (mPER) in benign and malignant biliary strictures. Methods: All cases with endoscopic retrograde cholangiopancreatography (ERCP) and plastic stent placement were retrospectively analyzed since establishing an elective replacement interval of every 6–8 weeks at our institution and mPER was determined. Results: A total of 3979 ERCPs (1199 patients) were analyzed, including 1262 (31.7%) malignant and 2717 (68.3%) benign cases, respectively. The median stent patency (mSP) was 41 days (range 14–120) for scheduled stent exchanges, whereas it was 17 days (1–75) for prematurely exchanged stents. The mPER was significantly higher for malignant (28.1%, 35–50%) compared with benign strictures (15.2%, 10–28%), P < 0.0001, respectively. mSP was significantly shorter in cases with only one stent (34 days [1–87] vs 41 days [1–120]) and in cases with only a 7‐Fr stent (28 days [2–79]) compared with a larger stent (34 days [1–87], P = 0.001). Correspondingly, mPER was significantly higher in cases with only one stent (23% vs 16.2%, P < 0.0001) and only a 7‐Fr stent (31.3% vs 22.4%, P = 0.03). Conclusion: A shorter replacement interval does not seem to lead to a clinically meaningful reduction of mPER in benign and malignant strictures. Large stents and multiple stenting should be favored as possible.